Prediction of Post-Traumatic Stress Disorder Symptom Severity Based on Perceived Social Support, Coping Styles, and Spiritual Well-Being in Survivors of a Fire Incident - Hatami Varzaneh, Abolfazl; Sheikh Rezaie, Zahra (Shahroud Journal of Medical Sciences, 2025)
Background: Post-traumatic stress disorder (PTSD) is one of the most debilitating psychiatric conditions, exerting long-lasting effects on mental health following severe traumatic events. This study aimed to examine the extent to which perceived social support, coping styles, and spiritual well-being predict PTSD symptom severity among university students who experienced psychological trauma during a fire incident in the course of the 2024 Arbaeen pilgrimage. Methods: Employing a descriptive-correlational design, a convenience sample of 102 students from universities in Qom, Iran, was recruited. Participants completed the Spiritual Well-Being Scale, the Billings and Moos Coping Styles Questionnaire, the Multidimensional Scale of Perceived Social Support, and the PTSD Checklist. Data were analyzed using descriptive statistics, Pearson’s correlation coefficients, and multiple regression analysis. Results: Results showed that existential well-being, problem-focused coping, and perceived social support from friends were negatively and significantly associated with PTSD symptom severity, whereas somatization-focused coping was positively and significantly related to higher PTSD severity. The regression model incorporating these variables accounted for 67% of the variance in PTSD symptoms. Conclusions: These findings highlight the crucial role of spiritual well-being and social support—particularly from friends—in preventing and reducing PTSD symptoms, and suggest that promoting adaptive coping strategies and strengthening supportive social networks may improve psychological outcomes among survivors of traumatic events.